Effect of Edible Film Glazing to Physico-Chemical, Microbial and Sensory Attributes of Frozen Pangasius Fillet - N. P. Minh (Journal of Global Pharma Technology, 2016)
Pangasius is a type of catfish that is endemic to the waters of Mekong basin in south-east Asia, belongs to the family Pangasiidae. It is generally processed to frozen fillets for domestic consumption and also exported to Europe and USA. Freezing and cold storage is an efficient method which preserves taste and nutritional value. Glazing is a process used to reduce undesirable drying or dehydration of fish during frozen or cold storage. Objective of the current research studied the feasibility of edible coating in maintaing and preserving the chemical, microbial and sensory attributes of frozen Pangasius fillet. The frozen Pangagius fillets were glazed by different formulas (N0: control or glazing with clean water; N1: 3% w/w chitosan and glycerol; N2: 3% w/w whey protein concentrate and glycerol; N3: 3% w/w alginate an glycerol; N4: 3% w/w carrageenan). The chemical quality was based on the analyzed results of ammonia (µNH3/g) and pH; biogenic amines such as putrescine (mg/kg), cadaverine (mg/kg), histamine (mg/kg), spermine (mg/kg), spermidine (mg/kg); lipid oxidation or malondialdehyde value (mg/kg); microorganism such as Total plate count (cfu/g), Enterobacteriaceae (cfu/g), Coliform (cfu/g), E. coli (cfu/g), Staphylococus (cfu/g), Listeria (cfu/g), Salmonella (cfu/g), Vibrio (cfu/g); sensory score. All treated frozen Pangagius fillets were tested after 12 months of storage. Results revealed that the incorporation of 3% w/w chitosan and glycerol in ice‐glazing could inhibit microbial spoilage and lipid oxidation and therefore maintain the freshness of Pangasius fillet during frozen storage. Under the optimal conditions, the shelf‐life of Pangasius fillet could be extended up to 12 months at −18 °C. The study indicated that the combination treatment with edible coating could be commercially utilized to maintain the freshness and prolong the shelf‐life of frozen Pangasius fillet.Keywords: Frozen, Pangasius fillet, Glazing, chitosan, Glycerol, Whey protein concentrate, Alginate, carrageenan.